MUSCL Type Schemes and Discrete Entropy Conditions (Journal of Computational Mathematics, 1997)
In this paper, the semi-discrete entropy conditions with so called the proper discrete entropy flux of a class of high resolution MUSCL type schemes are discussed for genuinely nonlinear scalar conservation laws. It is shown that the high resolution schemes satisfying such semi-discrete entropy conditions cannot preserve second order accuracy in the rarefaction region.